2021
DOI: 10.3389/fcell.2021.719351
|View full text |Cite
|
Sign up to set email alerts
|

Amlexanox and Forskolin Prevents Isoproterenol-Induced Cardiomyopathy by Subduing Cardiomyocyte Hypertrophy and Maladaptive Inflammatory Responses

Abstract: Chronic catecholamine stress (CCS) induces the occurrence of cardiomyopathy—pathological cardiac hypertrophy (PCH), which is characterized by left ventricular systolic dysfunction (LVSD). Recently, mounting evidence has implicated myocardial inflammation in the exacerbation of pathological cardiac remodeling. However, there are currently no well-defined treatment interventions or regimes targeted at both the attenuation of maladaptive myocardial hypertrophy and inflammation during CCS to prevent PCH. G protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 59 publications
(92 reference statements)
2
19
0
Order By: Relevance
“…This study aimed to explore the therapeutic potentials of AMLX in attenuating LVSD and facilitating recovery from ICM, as demonstrated in the AMI model ( 11 ). Also, we sought to, for the first time, explore if FSKN could enhance the recovery rates of the ICM model, as it stimulates the synthesis of cAMP, which is an essential modulator of cardiac and inflammatory responses ( 1 , 2 , 12 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study aimed to explore the therapeutic potentials of AMLX in attenuating LVSD and facilitating recovery from ICM, as demonstrated in the AMI model ( 11 ). Also, we sought to, for the first time, explore if FSKN could enhance the recovery rates of the ICM model, as it stimulates the synthesis of cAMP, which is an essential modulator of cardiac and inflammatory responses ( 1 , 2 , 12 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, AMLX treatment improved HR and systolic functions, which are consistent with Mo et al's findings ( 11 ). Nonetheless, our previous study found that when AMLX treatments were given simultaneously with ISO injections, AMLX's efficacy in attenuating LVSD was dampened ( 2 ). Hence, it is speculated that for AMLX treatment to be effective at attenuating LVSD in ICM, the sources of stressors must be obliterated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations